IMPLEMENTASI PENGELOLAAN SAMPAH DALAM UPAYA MENDUKUNG PROGRAM 3R (REDUSE, REUSE, RECYCLE): (Studi Bank Sampah Emak.Id Kecamatan Natar Kabupaten Lampung Selatan) - Fadilah Anggraeni; Rosidah Rosidah; Yuli Evadianti (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2026)
This study discusses the implementation, which is the process of executing a policy that has been formulated to achieve specific objectives, in the management of waste based on community involvement. Management here refers to the systematic efforts in planning, executing, and overseeing activities to ensure they are effective. In this context, the waste being managed refers to the remnants of daily human activities that need to be properly handled to prevent environmental contamination. The main focus of this research is the management of waste through the 3R program (Reduce, Reuse, Recycle), which is a principle for reducing waste by minimizing its generation (reduce), reusing items (reuse), and recycling waste materials (recycle). This program is implemented through Waste Banks, which are places for collecting and sorting waste that has economic value and can be exchanged for savings. The study was conducted at the Emak.Id Waste Bank in Natar District, South Lampung Regency, using a qualitative descriptive method with techniques such as observation, interviews, and documentation. The results show that the implementation of the 3R program has been carried out through community education, waste sorting training, and digitalization of waste transactions. However, challenges remain, including limited human resources, inadequate supporting facilities, and uneven public participation. Based on George C. Edwards III's policy implementation theory, the success of the policy is influenced by factors such as communication, resources, disposition, and bureaucratic structure. Therefore, strengthening coordination between stakeholders and raising public awareness is essential to support sustainable waste management. Keywords: Implementation; Management; Waste Management; Waste Bank; 3R Program